Karakteristik Ibu Hamil Dengan Risiko Tinggi di PMB Y Kota Bengkulu - Puji Astuti, Dwi; Tunggal Mutika, Winnie; damayanti, rini (Midwifery Science Care Journal, 2023)
Abstract: A high-risk pregnancy is a pregnancy that is likely to cause harm or complications to both the mother and the fetus during pregnancy, childbirth, or the puerperium when compared to normal childbirth and postpartum pregnancies. The purpose of this study is to determine high-risk pregnant women characteristics in PMB Y, Kampung Melayu, Padang Serai, Bengkulu, in 2020. The method used in this research is descriptive research with an observational research design. The sample to be taken in this study uses a total sampling of 173 pregnant women. In the results of data processing, univariate analysis is carried out, this analysis is aimed to obtain an overview of the frequency distribution of the various variables studied. The results of the study are as follows: 113 pregnant women based on the characteristics of the majority in the age range 20-35 years (76.9%), 116 high school education (67.1%), 65 nulliparous parity (37.6%), distance pregnancy ≥2 years are 103 people (59.5%), there is no history of abortion as many as 143 people (82.7%), height >145 cm are 157 people (90.8%), and LILA >23,5 cm are 145 people (83.8%). Conclusion: Pregnant women with high risk based on age <20 years and> 35 years are 40 people (23.2%), with a history of abortion as many as 30 people (17.3%), LILA <23,5 cm as many as 28 people (16.2%), height ≤145 cm as many as 16 people (9.2%), parity grand multipara as many as 13 people (7.5%), elementary education as many as 8 people (4.6%), and pregnancy spacing <2 years as many as 4 people (2.3%).